A RhxSy/C Catalyst for the Hydrogen Oxidation and Hydrogen Evolution Reactions in HBr. Issue 4 (10th February 2015) - Masud, Jahangir; Van Nguyen, Trung; Singh, Nirala; McFarland, Eric; Ikenberry, Myles; Hohn, Keith; Pan, Chun-Jern; Hwang, Bing-Joe
Abstract : Rhodium sulfide (Rh2 S3 ) on carbon support was synthesized by refluxing rhodium chloride with ammonium thiosulfate. Thermal treatment of Rh2 S3 at high temperatures (600°C to 850°C) in presence of argon resulted in the transformation of Rh2 S3 into Rh3 S4, Rh17 S15 and Rh which were characterized by TGA/DTA, XRD, EDX, and deconvolved XPS analyses. The catalyst particle size distribution ranged from 3 to 12 nm. Cyclic voltammetry and rotating disk electrode measurements were used to evaluate the catalytic activity for hydrogen oxidation and evolution reactions in H2 SO4 and HBr solutions. The thermally treated catalysts show high activity for the hydrogen reactions. The exchange current densities (io ) of the synthesized Rhx Sy catalysts in H2 -saturated 1M H2 SO4 and 1M HBr for HER and HOR were 0.9 mA/cm 2 to 1.0 mA/cm 2 and 0.8 to 0.9 mA/cm 2, respectively. The lower i o values obtained in 1M HBr solution compared to in H2 SO4 might be due to the adsorption of Br − on the active surface. Stable electrochemical active surface area (ECSA) of RhxSy catalyst was obtained for CV scan limits between 0 V and 0.65 V vs. RHE. Scans with upper voltage limit beyond 0.65 V led to decreased and unreproducible ECSA measurements.